2012
DOI: 10.1088/0022-3727/45/6/065201
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown study of dc silicon micro-discharge devices

Abstract: Abstract. The influence of geometrical and operating parameters on the electrical characteristics of dc micro-cavity discharges provides insight into their controlling physics. We present here results of such a study on silicon based micro-cavity discharge devices carried out in helium at pressure ranging from 100 to 1000 Torr. Different micro-reactor configurations were measured. The differences include: isolated single cavities versus arrays of closely spaced cavities, various cavity geometries (un-etched as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…It is known that the electrode material shape and structure affect the U B . The SEE, γ , of the material, which provides information on the efficiency of electron emission from the cathode due to ion bombardment, can have a large impact on the U B . In addition, the nanoporous structure of zeolite might also influence on the electron emission and consequently on the U B .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the electrode material shape and structure affect the U B . The SEE, γ , of the material, which provides information on the efficiency of electron emission from the cathode due to ion bombardment, can have a large impact on the U B . In addition, the nanoporous structure of zeolite might also influence on the electron emission and consequently on the U B .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the interaction of the discharge with a dielectric surface requires the study of secondary processes at the dielectric surface. It should be noted that the secondary emission coefficient (SEE), γ , of the material, can have a large impact on the U B . In most studies of surface DBDs, SEE due to ion bombardment are considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy conversion from the cathode for an incident ion can be evaluated by studying f esc . [18][19][20] Indeed, an external field can also occur and propagate in the gas volume. Thus, the electrons lead to a certain spatiotemporal distribution below the breakdown voltage.…”
Section: Theorymentioning
confidence: 99%
“…21,22 SEE attracts attention because of the important applications of such microdevices, including microelectromechanical systems, semiconductor devices, excimer sources, plasma display panels, lasers, electron multipliers, etc. [23][24][25] According to recent studies, the importance of emission processes from a surface and of electron-induced collisional transfer has increased in the framework of SEE; For instance, Ref. 21 showed that SEE levels for various gas media change with E/N, where E and N are the electrical field and gas density, respectively.…”
Section: Theorymentioning
confidence: 99%